Assessment of the functional state of the chewing muscles in patients with a changeable bite who use chewing gum - M. V. Kabytova; K. Yu. Tkalina; Yu. A. Makedonova; E. N. Iarygina; L. A. Devyatchenko (Эндодонтия Today, 2024)
INTRODUCTION. The relevance of the study is related to the increased uncontrolled consumption of chewing gum by children.AIM. The aim is to study the functional state of masticatory muscles in patients with changeable dentition using chewing gum in different modes.MATERIALS AND METHODS. The study was carried out on 31 children, the average age of whom was 8.5 ± 1.2 years. It is at this age there is an active formation of facial morphology, which is directly related to the activity of the masticatory muscles. Therefore, it is very important to assess the condition of the masticatory musculature in order to timely identify imbalance in muscle activity, hypo and hypertonus of the musculature and to start therapy. Electromyographic study was performed on the Synapsis apparatus.RESULTS. There is a violation of coordination in the work of masticatory muscles with predominance in the work in the right temporal muscle and left proper masticatory muscle. This is due to the fact that additional chewing was present in this group.CONCLUSION. The provided analysis of masticatory function showed that children who frequently use chewing gum have a pronounced discoordination and imbalance in the work of masticatory muscles.